PEMAHAMAN KONSEPTUAL SISWA DIKAJI DARI TAKSONOMI SOLO DALAM MATERI FUNGSI EKSPONENSIAL DI SMA - Sri Asih Agustin; Sugiatno Sugiatno; Dede Suratman (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research is to explain the conceptual understanding of students refer to SOLO taxonomy in the material of exponential function at SMA Negeri 3 Pontianak. The research method used is explorative descriptive method. The subject of the research are 10 students class of X IPA 6 in SMA Negeri 3 Pontianak. Subject taking was done by giving a SOLO taxonomy test first and then each of the 2 subjects selected representing each of the SOLO taxonomy levels was selected. The technique of collection data used are written tests and interviews. The tools of collection data used are test instrument, interview guide, voice recorder, and camera. The result of the data analysis of this research showed that students conceptual understanding of SOLO taxonomy is very low category with a percentage of 54%. The students conceptual understanding of level 0, level 1, and level 2 is very low category with a percentage of 34%, 44%, and 53%. Meanwhile, level 3 is low category with a percentage of 59%. Furthermore, level 4 is high category with a percentage of 81%. Keywords: Conceptual Understanding, Solo Taxonomy, Exponential Function